A Simple Surgical Solution for Functional Improvement of Deforming Vascular Malformations with Lip Involvement. Issue 2 (17th February 2023) - King, Brody W.; Anderson, Eric W.; Sudduth, Jack D.; Marquez, Jessica L.; Dunklebarger, Mitch; Collar-Yagas, Lucia; Gociman, Barbu
Abstract : Summary: The management of large, deforming facial arteriovenous malformations (AVMs) can be a daunting clinical challenge for patients and surgeons. Many patients delay treatment due to fear of surgical intervention and concern for unfavorable cosmetic outcomes. Delaying treatment can lead to soft-tissue hypertrophy. Occasionally, facial AVMs can also present with lip involvement, necessitating surgical intervention. A major potential issue regarding AVMs managed with surgical excision is excessive bleeding due to the enlarged dermal vascular plexus. Here, we present a simple surgical technique used to manage deforming AVMs involving the lips. A 32-year-old man with Sturge-Weber syndrome and a 72-year-old man with AVMs of the left face presented to clinic for management. The malformations involved the lips in both patients. Both patients had constant drooling and difficulty eating and talking, in addition to aesthetic concerns. They both underwent surgical excision of the redundant tissue with minimal undermining, advancement flaps, and layered closure. Minimal undermining allowed successful removal of the AVMs and redundant tissue without excessive blood loss and allowed healing without complications. Both patients had significant improvement in eating and talking without drooling. Aesthetically, satisfactory outcomes were maintained at 1-year follow-up appointments. Removal of AVMs while minimizing blood loss can be a challenging endeavor. Here, we have presented a successful, effective technique for restoring both form and function in patients with AVMs involving the lips, with good long-term results.